Assessment of knowledge, attitudes and practices toward prevention of hepatitis B virus infection among healthcare workers of Mashhad University of Medical Sciences, Iran - Barzegar, Afsoon; Rahimpour, Farzaneh; Najaf Najafi, Mona; Naderi, Hamidreza; Afshari Saleh, Lahya (International Journal Of Community Medicine And Public Health, 2022)
Background: Hepatitis B virus (HBV) infection is regarded as one of the most significant occupational hazards threatening healthcare workers (HCWs). Moreover measuring knowledge, attitudes, and practices among these individuals can be assumed as one of the most important activities to develop the preventive strategies of HBV infection. Methods: This cross-sectional study was conducted in 2017 on HCWs of teaching hospitals affiliated to MUMS. Stratified sampling method was used and the knowledge-attitude-practice questionnaire was reproduced and distributed among nine groups of HCWs based on the proportion of the individuals working in each occupational category. Then knowledge, attitudes, and practices in different sub-groups were compared using independent samples T-test or analysis of variance or even via their non-parametric equivalents. Results: This study was performed on 681 individuals with a mean age of 30.9±6.01 years. The results also showed that 448 HCWs (79.0%) had good levels of knowledge, 389 individuals (69.5%) were endowed with favorable levels of attitudes, and 391 of them (74.9%) had good levels of practices. According to the results of Spearman’s rank-order correlation, there was only a significant but weak correlation between knowledge and attitudes (p=0.00, r=0.16). Conclusions: Based on the findings of this study, it seemed that the levels of knowledge among HCWs of MUMS was good, although about a fifth of these individuals required upgrading their status in terms of their levels of knowledge about HBV. In general, according to the results obtained from the parameters of attitudes and practices, it was assumed that levels of education concerning HBV infection were in need of improvements.